Current pharmacotherapy and diagnostic methods of Pompe Disease in Poland - Dominika Anna Janeczko (Journal of Education, Health and Sport, 2019)
Pompe disease is estimated to happen in 1 out of 40 000 borns. It is rare metabolic disease connected to autosomal recessive genetic mutation. Disease is characterised by deficit of α-glucosidase (GAA) which is lysosomal glycogen hydrolizing enzyme acid. Decreased activity of enzyme leads to glycogen storage in lysosomes which appears as disfunction of tissues, especially cardiac muscle and skeletal muscles. In Poland, we have two common and very simple methods to diagnose Pompe disease. First test is dried blood spot (DBS), second is full peripheral blood test. Currently, in Poland, drug containing alglucosidase alpha is refunded. Drug is available as powder for infusion. Periodic assessment of therapy effectiveness is performed at least every 6 months based on rating the patient's clinical condition and assessment of the effectiveness of the therapy used.